Evidence of phenotypic plasticity along an altitudinal gradient in the dung beetle Onthophagus proteus - Roisin A. Stanbrook; W. Edwin Harris; Charles P. Wheater; Martin Jones (PeerJ, 2021)
Background High altitude insects are an ecologically specialized group and possess a suite of adaptions which allow persistence in the inhospitable conditions often associated with mountain tops. Changes in body coloration and reductions or increases in body size are thought to be examples of such adaptions. Melanic individuals, or individuals containing high levels of eumelanin, possess several traits which increase resistance to ultraviolet radiation and desiccation, while aiding thermoregulation. Trait variation is often observed in dung beetles and is associated with dimorphism and sexual selection. In this study, we identified trait changes which occur across an altitudinal gradient by measuring morphological color and body size traits in a montane insect. Methods Using standard digital photography and Image J, we examined individuals of Afromontane dung beetle Onthophagus proteus. Individuals were classified according to sex and color morph to identify intrasexual variance. Nine morphometric traits were measured per beetle to identify patterns of morphology across discrete 500 m altitude segments. Results The results of this study provide one of the first descriptions of trait changes associated with elevation in an African dung beetle. We suggest that color polymorphism in Onthophagus proteus might be at least partly driven by environmental factors as there is significantly increased melanism with increasing elevation and significant differences in color hues between altitude bands. We also suggest changes in horn length are density dependent, as we observed an increase in cephalic horn length at high elevations where O. proteus is the most abundant species.